Rio Grande do Sul native pasture iron and manganese content - Gavillon, Olga; Quadros, Alena Theresa (Pesquisa Agropecuaria Brasileira, 2014)
Data on the iron and manganese contents in spring and summer native pastures, in Rio Grande do Sul, are presented. The statistical analysis showed a significant decrease in iron content, and also of the iron/manganese ratio, from spring to summer, but there was no significant difference in manganese content between those two seasons. The frequency distribution showed the iron values to be lower than those of manganese, with an even more unfavorable relationship in summer due to the decrease in iron content in this season. In the 154 analysed samples, all iron contents were above ruminant requirements. There is, however, a remote possibility of iron deficiency due to manganese interference in the zones where iron content is below 150 ppm and manganese content is above 400 ppm. The manganese content was frequently very high but never reached the toxic levels reported in the literature.